2015
DOI: 10.1155/2015/456858
|View full text |Cite
|
Sign up to set email alerts
|

The Results of Adductor Magnus Tenodesis in Adolescents with Recurrent Patellar Dislocation

Abstract: Recurrent dislocation of the patella is a common orthopaedic problem which occurs in about 44% of cases after first-time dislocation. In most cases of first-time patellar dislocation, the medial patellofemoral ligament (MPFL) becomes damaged. Between 2010 and 2012, 33 children and adolescents (39 knees) with recurrent patellar dislocation were treated with MPFL reconstruction using the adductor magnus tendon. The aim of our study is to assess the effectiveness of this surgical procedure. The outcomes were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…All 3 MPFL reconstruction techniques specific to the skeletally immature athlete have been shown to be safe with a low rate of recurrent dislocation and morbidity. Malecki et al 29 demonstrated a 10% risk of recurrent of patellofemoral instability at 2.6 years in 33 skeletally immature patients using the adductor transfer technique. Sillanpää et al 45 found a 14% risk of recurrence at 8 years in a study comparing adductor transfer to the Roux Goldthwait distal soft tissue realignment procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All 3 MPFL reconstruction techniques specific to the skeletally immature athlete have been shown to be safe with a low rate of recurrent dislocation and morbidity. Malecki et al 29 demonstrated a 10% risk of recurrent of patellofemoral instability at 2.6 years in 33 skeletally immature patients using the adductor transfer technique. Sillanpää et al 45 found a 14% risk of recurrence at 8 years in a study comparing adductor transfer to the Roux Goldthwait distal soft tissue realignment procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The close proximity of the MPFL femoral insertion to the adductor tubercle has led others to use the adductor tendon for MPFL reconstruction, thus avoiding the need for a bony socket or fixation on the femoral side. 29,44,45 Sillanpää et al 44,45 has described utilizing the adductor tendon to re-create the MPFL by cutting the tendon 10 cm proximally and rerouting this tendon to the medial patella (''adductor transfer''). Dissection of the adductor magnus tendon can result in neurovascular injury given the proximity of the tendon to the adductor hiatus, saphenous nerve, and geniculate arteries 21 .…”
mentioning
confidence: 99%
“…Donor-site tenderness and muscle retraction were outlined by previous authors as potential complications of this technique, but only in cases when there was a need to harvest the full volume of the tendon. 28,32,50,51 Similar complications have been reported in reconstruction techniques of other ligaments with the use of various tendinous graft sources (ie, quadriceps, semitendinosus, gracilis tendons). However, we strongly believe that the remaining volume, intact aponeurotic attachment, and medial intermuscular septum integrated with the fibers of the membranous segment of the tendon provide sufficient pull on the AT and minimize the possibility of postoperative muscle retraction.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, none of the previous studies that investigated the clinical outcomes of AT-MPFL cited the aforementioned postoperative complications. 10,32,49 During the anatomic evaluation, it was determined that the distance from the femoral insertion of the AT on the tubercle to the hiatus, measured at 10.8 6 1.3 cm, well exceeds the length of the native MPFL and that of the desired length of the graft at 7.5 6 0.5 cm. In other words, when the predetermined length of the graft was harvested, the hiatus was never reached; thus, the risk of an injury to the neurovascular structures remained minimal to none.…”
Section: Discussionmentioning
confidence: 99%
“…
Within the literature, a great deal of space has been devoted to operating techniques and the overall results of the treatment of recurrent patellar dislocation with MPFL, which is gaining popularity in recent times. [1][2][3][4][5][6][7] The MPFL plays a crucial role as a passive stabilizer of patella at 20 to 30 degrees of flexion and, along with the conditions of the anatomical shape of the femoral-patellar joint and the function of quadriceps, influences the overall patellar stability. 8-14 However, only a few studies have examined indirectly or directly the function of quadriceps with the help of gait analysis, 15,16 electromyography (EMG) evaluation, 2,13,17 isokinetic test, 5,6,12,18-21 and proprioception 22,23 in the case of recurrent patellar dislocation.
…”
mentioning
confidence: 99%